Strategi Guru Pendidikan Agama Islam Dalam Menginternalisasikan Nilai Moderasi Beragama Melalui Pembelajaran dan Kurikulum ISMUBA di Sekolah Menengah Pertama Universitas Muhammadiyah Purwokerto - Sab'ati Mela Matsania; M. Sidiq Pambudi (Jurnal Eduslamic, 2026)
The rapid development of digital media has increased students’ exposure to diverse religious narratives, creating challenges for Islamic Religious Education teachers in fostering balanced and tolerant religious attitudes. This study aims to analyze the strategies employed by Islamic Religious Education teachers in instilling religious moderation values among students at Junior High School Universitas Muhammadiyah Purwokerto. A qualitative case study approach was employed using participatory observation, in-depth interviews, and document analysis. Data were analyzed through the interactive model of Miles, Huberman, and Saldaña. The findings indicate that teachers promote religious moderation through lesson planning, dialogical and contextual learning, critical digital literacy, teacher role modelling, and the implementation of the ISMUBA curriculum. These strategies strengthen students’ tolerant, inclusive, and balanced religious attitudes, demonstrating that integrating pedagogical practices with the ISMUBA curriculum effectively reinforces religious moderation in Muhammadiyah schools.